"A sense of life": the abstruse language of taste in Chinese culture. (1st January 2023) - Zhang, Jinghong
ABSTRACT: This article examines the Chinese language of taste – characterized by abstruseness and obscurity – based on ethnographic investigation, and the reading of historical sources on tea drinking. Abstract terms such as qi and yun have long been applied to tea within Chinese culture, and the ideas that underlie them are rooted in basic understandings of food, politics, cosmology, and esthetics. They manifest notions concerning the integration of humans with objects, body with mind, and gustatory appreciation with esthetic perception. I illustrate how the abstruse expression for the taste of tea continues to be in practice in contemporary Chinese society. In addition, I demonstrate how this abstruseness of "taste" is also present in cross-sensorial contexts, namely in Chinese representations of the olfactory, auditory and visual. I argue that such abstruse expression incorporates emotional, esthetic and creative interpretation, and shows an affective rather than taxonomic understanding of the world.